Pemulihan Aset Tindak Pidana Korupsi Melalui Non-Conviction Based Asset Forfeiture - Wahyu Sinta Dewi Pramudita; Ali Masyhar Mursyid; Cahya Wulandari (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
This study analyzes the dialectic of political interests in the recovery of assets from corruption through the Non-Conviction Based Asset Forfeiture (NCB) mechanism. Using a normative legal approach, the study reveals that NCB is a strategic solution to overcome the limitations of the conventional system, especially in cases where perpetrators flee or have immunity, with the potential to increase asset recovery by up to 40%. Findings indicate that political interests are hindering the enactment of the Asset Forfeiture Bill, despite NCB being mandated by the UNCAC 2003 and proven effective internationally. This study recommends accelerating the legislative process for the enactment of the Asset Forfeiture Bill, which could revolutionize the enforcement of criminal law against corruption in Indonesia